The international law of property - Sprankling, John G., 1950- (Oxford : Oxford University Press, 2014)
International law increasingly creates, harmonizes, and restricts property rights, thereby superseding national law. This book examines this emerging regime of international property law. Looking at the intersection between international law and private property, the work argues that a global right to property should be recognized.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on May 20, 2014).
Keywords: Property; International law